Who mocks whom? From today's buffoons to revisited techniques (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article aims to share reflections on the buffoons’ place in society, based on the meaning of the term. In addition, it discusses ethical issues in buffa performance. Supported by authors and artists such as Beth Lopes, Henry Bergson, José Tonezzi, Leo Bassi, among others, this text rubs many layers of mocking laughter, linking it to the social and historical recognition of these figures in order to introduce a problematization about the techniques developed by the French pedagogues Jacques Lecoq and Philippe Gaulier, focusing on their implications over creative processes.
Keywords: Buffoonery; Performativity; Laughter; Technique